Scandalous denouncement: discrimination, difference, and queer scandal in urban Amazonian Peru. Issue 1 (2nd January 2022) - Perez, Justin
ABSTRACT: Over the course of the 2010s, one objective of HIV prevention efforts in Peru's Amazonian region has been to mitigate the adverse effects of discrimination on transgender communities. Some of the technical experts implementing these efforts in the city of Tarapoto referred to 'cultivating a culture of denouncement' as a shorthand for this objective. This article juxtaposes two experiences of discrimination and subsequent efforts at seeking redress. While both involve trans women who were denied entry into a nightclub, one case was converted into a successful discrimination grievance while the other case was never formally codified as such. Ethnographic analysis of Yesika's 'unsuccessful' case suggests that the imperative to file formal discrimination grievances as a form of HIV prevention, though intended to mitigate exclusion, paradoxically reinforces ethno-racial hierarchies, obscures the willful inaction of auxiliary municipal police, and subjects those who attempt denouncement to intensified allegations of being 'scandalous.' Yesika's scandalous denouncement thus makes visible how preventing HIV is embedded in existing configurations of ethno-racial, gender, and sexual difference.